The Combined Boris-Cyclotronic Integrator for Axially Symmetric Penning Ion Source Simulation - Ahsani Hafizhu Shali; Muhamad Rangga Del Piero (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2025)
An investigation of the use of combined boris-cyclotronic particle integrator scheme for 2D axially symmetric Penning ion source simulation program has been performed. The particle-in-cell based simulation program was intended to be used for Penning ion source optimization. The combination was done by using cyclotronic integrator in cylindrical coordinates while ions were integrated using Boris algorithm (Boris-Cyclotronic scheme). The investigation was centered around the claim that cyclotronic integrator is not limited by gyration period constraints, unlike Boris algorithm. As a benchmark, this scheme is compared against the standard approach in which both species are integrated using the Boris algorithm (All-Boris scheme). The plasma sustainability result shows that for regions where time step width is smaller than the gyration period, Boris-Cyclotronic algorithm is indistinguishable from All-Boris algorithm. For time step width comparable to gyration period, there is an increase in electron production in Boris-Cyclotronic algorithm while All-Boris algorithm remains the same. Single-particle tests show that although the Boris integrator produces noisy trajectories, it maintains a bounded energy error and a consistent average path. In contrast, the cyclotronic integrator produces smoother trajectories but introduces significant oscillatory energy gain, which leads to artificial ionization and exaggerated electron production. These findings indicate that despite its less accurate individual trajectories, the All-Boris scheme provides more physically consistent results for Penning ion source simulation than the Boris–Cyclotronic scheme